The Arabidopsis NPF3 protein is a GA transporter - Tal, Iris; Zhang, Yi; Jørgensen, Morten Egevang; Pisanty, Odelia; Barbosa, Inês C. R.; Zourelidou, Melina; Regnault, Thomas; Crocoll, Christoph; Erik Olsen, Carl; Weinstain, Roy; Schwechheimer, Claus; Halkier, Barbara Ann; et al. (Nature communications, 2016)
Gibberellins (GAs) are plant hormones that promote a wide range of developmental processes. While GA signalling is well understood, little is known about how GA is transported or how GA distribution is regulated. Here we utilize fluorescently labelled GAs (GA-Fl) to screen for Arabidopsis mutants deficient in GA transport. We show that the NPF3 transporter efficiently transports GA across cell membranes in vitro and GA-Fl in vivo . NPF3 is expressed in root endodermis and repressed by GA. NPF3 is targeted to the plasma membrane and subject to rapid BFA-dependent recycling. We show that abscisic acid (ABA), an antagonist of GA, is also transported by NPF3 in vitro. ABA promotes NPF3 expression and GA-Fl uptake in plants. On the basis of these results, we propose that GA distribution and activity in Arabidopsis is partly regulated by NPF3 acting as an influx carrier and that GA–ABA interaction may occur at the level of transport. Transport of the plant hormone gibberellin is required for normal plant growth and development. Here, Tal et al . show that NPF3 is able to transport gibberellin in vitro , and provide evidence that it is required for normal gibberellin distribution and activity in plants.